Comunidades raciais no Brasil: uma análise dos efeitos de raça e classe nas atitudes raciais dos brasileiros - Nathalia Franca Figueredo Porto (2016)
This dissertation aims at understanding the adscriptive and socioeconomic determinants of brazilian racial public opinion in two basic dimensions: principles and values; and race-targeted policies. During the last years, many studies have made widely relevant theoretical and empirical contributions on racial relations in Brazil, and some of them highlight racial identity as a powerful predictor of racial public opinion, joined by class and status. In spite of this, little has been said on the effects of race and socioeconomic features altogether on how people reason towards race. This research intends to contribute to this debate, working with the hypothesis that racial attitudes in Brazil are a product of a combination between race and socioeconomic features. Relying on Racismo Cordial survey data (2008), one of our main findings state that race is importante to explain oscilations in racial attitudes in Brazil, contrary to what previous theoretical works have stated. Results also show that income and Education are positively associated to racial tolerance, but negatively associated to the support for racial quotas in brazilian public universities. Our interpretation of this so-called contradiction is that, whereas the support for racial principles has racial solidarity as a bedrock, individual and collective interests are what motivates support for race-targeted policies.